2008
DOI: 10.1073/pnas.0801073105
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellites as EWS/FLI response elements in Ewing's sarcoma

Abstract: The ETS gene family is frequently involved in chromosome translocations that cause human cancer, including prostate cancer, leukemia, and sarcoma. However, the mechanisms by which oncogenic ETS proteins, which are DNA-binding transcription factors, target genes necessary for tumorigenesis is not well understood. Ewing's sarcoma serves as a paradigm for the entire class of ETS-associated tumors because nearly all cases harbor recurrent chromosomal translocations involving ETS genes. The most common translocatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
352
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(381 citation statements)
references
References 26 publications
14
352
6
Order By: Relevance
“…Consistent with previous microarray experiments, RNAseq analysis identified a large number of genes repressed by EWS-FLI1 (8,16). Direct activation of gene expression by EWS-FLI1 occurs via binding to a consensus motif near promoters or by binding to a distal microsatellite repeat (57,58). To date, the mechanisms responsible for EWS-FLI1-mediated repression remain unclear.…”
Section: Methodssupporting
confidence: 59%
“…Consistent with previous microarray experiments, RNAseq analysis identified a large number of genes repressed by EWS-FLI1 (8,16). Direct activation of gene expression by EWS-FLI1 occurs via binding to a consensus motif near promoters or by binding to a distal microsatellite repeat (57,58). To date, the mechanisms responsible for EWS-FLI1-mediated repression remain unclear.…”
Section: Methodssupporting
confidence: 59%
“…Translocations with other ETS genes are detected in most of the remaining tumors, yielding similarly functioning fusion proteins (16). We recently found that, despite conservation of the ETS DNA binding domain, the fusion oncoprotein uniquely localizes to specific microsatellite regions (17,18). Using formaldehyde-assisted isolation of regulatory elements (FAIRE), a biochemical strategy to enrich for nucleosome-depleted regions of chromatin, we demonstrated that EWSR1-FLI1 binding was necessary to maintain nucleosome depletion at these sites.…”
mentioning
confidence: 99%
“…In addition, even in the context of well characterized matrices, pattern matching methods do not take into account the possible effect of other proteins in the transcriptional complex, which may redirect or facilitate the binding of the transcription factor under study to DNA sequences not represented in the consensus matrix. [42][43][44] In this regard, a recent study on the E2F-binding specificity confirmed the fact that only a small percentage of the regions bound in vivo by E2F factors actually contain the E2F consensus motif. 45 Pattern detection methods search for recurring and overrepresented DNA motifs in specific subsets of sequences, such as genomic regions identified by ChIP-chip or ChIP-seq, as bound by a given transcription factor.…”
Section: Identification Of Transcription Factor-binding Sitesmentioning
confidence: 64%
“…45 Pattern detection methods search for recurring and overrepresented DNA motifs in specific subsets of sequences, such as genomic regions identified by ChIP-chip or ChIP-seq, as bound by a given transcription factor. 42,46 Pattern detection techniques can be used to identify putative DNA-binding motifs for transcription factors without previous knowledge of their DNA-binding properties and for the discovery of neighbor cooperating motifs specifically enriched in coregulated sets of genes.…”
Section: Identification Of Transcription Factor-binding Sitesmentioning
confidence: 99%